2008
DOI: 10.1007/s00418-008-0425-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of serine protease inhibitor kazal type 3 (Spink3) during mouse embryonic development

Abstract: Recent evidence shows that the serine protease inhibitor Kazal type 3 (Spink3) has more diverse functions than expected. To gain insight into its function, we analyzed the spatiotemporal expression profile of Spink3, using in situ hybridization (ISH) and a Spink3+/lacZ knock-in mouse, in which lacZ was inserted into the Spink3 locus. Spink3lacZ expression was first observed in the foregut, midgut, hindgut and the forebrain/midbrain junction region at 9.5 days post coitus (dpc). In the pancreas, Spink3 mRNA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 30 publications
(30 reference statements)
5
30
1
Order By: Relevance
“…However, when the gastrointestinal tract is inflamed, SPINK1 is involved in the regenerative process at the gastric ulcer edge and is strongly expressed within the ulcer-associated cell lineage in patients with IBD (11,12). In addition, we also observed Spink3 in the large intestine at 11.5 days postconception, an earlier stage of development, thus Spink3 influences the proliferation of colonic epithelial cells (8). Furthermore, Ogawa and colleagues (13,14) found elevated serum SPINK1 levels in patients with severe systemic inflammation.…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…However, when the gastrointestinal tract is inflamed, SPINK1 is involved in the regenerative process at the gastric ulcer edge and is strongly expressed within the ulcer-associated cell lineage in patients with IBD (11,12). In addition, we also observed Spink3 in the large intestine at 11.5 days postconception, an earlier stage of development, thus Spink3 influences the proliferation of colonic epithelial cells (8). Furthermore, Ogawa and colleagues (13,14) found elevated serum SPINK1 levels in patients with severe systemic inflammation.…”
Section: Introductionsupporting
confidence: 67%
“…In the gastrointestinal tract, Spink3 is most strongly expressed in the sigmoid colon and rectum at the embryonic stage (8). In addition, we previously revealed that the epithelial of the duodenum and small intestine in Spink3 À/À mice were degenerated (5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations